Evolutionary conserved light regulation of Calvin cycle activity by NADPH-mediated reversible phosphoribulokinase/CP12/ glyceraldehyde-3-phosphate dehydrogenase complex dissociation - Wedel, Norbert (The National Academy of Sciences, 1998)
For higher plant chloroplasts, two key enzymes of the Calvin cycle, phosphoribulokinase (EC 2.7.1.19) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH, EC 1.2.1.13), have recently been shown to be oligomerized onto the nonenzymatic peptide CP12. Enzymatic activity depends on complex dissociation, mediated by NADPH. The discovery of genes for CP12 in mosses, green algae, and cyanobacteria, together with the analysis of equivalent multiprotein complexes of Chlamydomonas and Synechocystis suggests that light regulation of Calvin cycle activity via NADPH-mediated reversible phosphoribulokinase/CP12/GAPDH complex dissociation is conserved in all photosynthetic organisms, prokaryotes and eukaryotes. In vitro complex reconstitution assays with heterologously expressed Synechocystis wild-type and mutagenized CP12 demonstrate a conserved subunit composition, stoichiometry, and topology in this complex. Further finding of genes, coding for chimeric proteins, carrying CP12 or parts of it as genetic fusions, indicates that evolution has used the peptide loops of CP12 as universal modules to keep various enzymatic activities under the control of NADP(H). These fusion events occurred at least twice in evolution. First was the fusion of the duplicated genes for CP12 and the ORF4 protein of Anabaena variabilis to the chimeric gene for the heterocyst-specific expressed ORF3 protein, most probably involved in N(2) fixation. A second gene fusion, which led to the higher plant chloroplast-specific GAPDH subunit, GAPB, has taken place during the transition from water- to land plants.